1967
DOI: 10.1017/s000335610003823x
|View full text |Cite
|
Sign up to set email alerts
|

The protein requirement of the ruminant calf. I. The effect of protein content of the concentrate mixture on the performance of calves weaned at an early age

Abstract: 1967). The protein requirement of the ruminant calf. I. The effect of protein content of the concentrate mixture on the performance of calves weaned at an early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
8
3

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
7
8
3
Order By: Relevance
“…Stobo, Roy & Gaston (1967) reported that in the ruminating calf a given amount of protein supports a greater body-weight gain with a greater efficiency of food utilization when supplied with a large compared to a small amount of energy. Stobo & Roy (1973) generalized their evidence, and agreed broadly with the above interpretation.…”
supporting
confidence: 70%
“…Stobo, Roy & Gaston (1967) reported that in the ruminating calf a given amount of protein supports a greater body-weight gain with a greater efficiency of food utilization when supplied with a large compared to a small amount of energy. Stobo & Roy (1973) generalized their evidence, and agreed broadly with the above interpretation.…”
supporting
confidence: 70%
“…This result is similar to that observed by BROWN et al6) In contrast, STOBO et al 7) has reported that the addition of urea to the low-protein diet did not result in increased daily nitrogen retention. This could probably be due to the fact that the level (about 12%) of pre-contained protein in the diet to which urea was added was too high to obtain a response with urea supplementation, as stated by STOBO et al7) Incidentally, this is about 9% in this experiment and about 7% in the study by BROWN et al 6) BROWN et al 6) found that calves fed with urea retained slightly less nitrogen than those fed with linseed meal, but that this difference was not significant.…”
Section: Discussionsupporting
confidence: 90%
“…LEIBHOLZ and NAYNOR8) reported that daily nitrogen retention of calves on a diet supplemented with urea was equal to that of those on a diet supplemented with meat meal. On the other hand, KAY et al9) and STOBO et al 7) reported independently that the nitrogen retention was significantly lower for calves on diet supplemented with urea than for those on positive control diet. Thus, the results of studies done so far on the extent of nitrogen retention in the calves under 3 months of age that were given a diet in which the main protein supplement has been replaced by urea were very variable.…”
Section: Discussionmentioning
confidence: 97%
“…IT was concluded from our earlier experiments (Stobo, Roy and Gaston, 1967) that, for maximum live-weight gain to be achieved by calves up to the age of 12 weeks, the protein content of the concentrate must exceed 11-9% on an air-dried basis up to 8 weeks, but need not be greater than this level after 8 weeks of age. To test the validity of this conclusion, an experiment was made to investigate the effect on calf performance of changing the protein content of the concentrate under ad libitum feeding conditions (Experiment 4).…”
mentioning
confidence: 90%